Jazz in China : from dance hall music to individual freedom of expression - Marlow, Eugene (University Press of Mississippi, 2018)
"Is there jazz in China? This is the question that sent author Eugene Marlow on his quest to uncover the history of jazz in China. Marlow traces China's introduction to jazz in the early 1920s, its interruption by Chinese leadership under Mao in 1949, and its rejuvenation in the early 1980s with the start of China's opening to the world under Premier Deng Xiaoping. Covering a span of almost one hundred years, Marlow focuses on a variety of subjects--the musicians who initiated jazz performances in China, the means by which jazz was incorporated into Chinese culture, and the musicians and venues that now present jazz performances. Featuring unique, face-to-face interviews with leading indigenous jazz musicians in Beijing and Shanghai, plus interviews with club owners, promoters, expatriates, and even diplomats, Marlow marks the evolution of jazz in China as it parallels China's social, economic, and political evolution through the twentieth and into the twenty-first century. Also featured is an interview with one of the extant members of the Jimmy King Big Band of the 1940s, one of the first major all-Chinese jazz big bands in Shanghai. This book is a cultural history that reveals the inexorable evolution of a democratic form of music in a Communist state."--Provided by publisher.